Occlusal Characteristics of Primary Dentition in Sudanese Children in Khartoum State - Amal H. Abuaffan; Roa Mohammed Abd-Alrahman (Brazilian Dental Science)
Objective: To determine the occlusal characteristics feature of primary dentition in a group of Sudanese children.